Development of agility utilising a multidimensional modality of plyometrics - Wagner, M. C.; Oden, G. L.; Glave, A. P.; Hyman, W. V. (Journal of Fitness Research, 2014)
Introduction: Most sports demand different aspects of movement in order to be successful. Training methods have attempted to improve different areas, and much of the focus has recently been on improving speed, agility and quickness (SAQ). Various types of plyometric training have been utilised in order to increase SAQ. However, the dimensional aspect of training has not been well researched.